2000
DOI: 10.1073/pnas.97.17.9695
|View full text |Cite
|
Sign up to set email alerts
|

Ca 2+ -dependent regulation of synaptic SNARE complex assembly via a calmodulin- and phospholipid-binding domain of synaptobrevin

Abstract: Synaptic core complex formation is an essential step in exocytosis, and assembly into a superhelical structure may drive synaptic vesicle fusion. To ascertain how Ca 2؉ could regulate this process, we examined calmodulin binding to recombinant core complex components. Surface plasmon resonance and pull-down assays revealed Ca 2؉ -dependent calmodulin binding (Kd ‫؍‬ 500 nM) to glutathione Stransferase fusion proteins containing synaptobrevin (VAMP 2) domains but not to syntaxin 1 or synaptosomal-associated pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

8
96
0
1

Year Published

2001
2001
2014
2014

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 96 publications
(105 citation statements)
references
References 36 publications
(43 reference statements)
8
96
0
1
Order By: Relevance
“…We therefore tested whether calmodulin does indeed bind to synaptobrevin in a calcium-dependent manner, and if so, whether binding was preserved when synaptobrevin is reconstituted into liposomes. When calmodulin and synaptobrevin (lacking the transmembrane domain) were mixed, a Ca 2ϩ -dependent increase in tryptophan fluorescence emission, associated with a slight blue shift, was observed ( Figure 4B), thus confirming the previous findings by Quetglas et al (2000). In addition, no effect of Ca 2ϩ /calmodulin on SNARE complex formation was observed (Supplementary Figure S3).…”
Section: Binding Of Ca 2؉ /Calmodulin To Synaptobrevin Does Not Altersupporting
confidence: 79%
See 1 more Smart Citation
“…We therefore tested whether calmodulin does indeed bind to synaptobrevin in a calcium-dependent manner, and if so, whether binding was preserved when synaptobrevin is reconstituted into liposomes. When calmodulin and synaptobrevin (lacking the transmembrane domain) were mixed, a Ca 2ϩ -dependent increase in tryptophan fluorescence emission, associated with a slight blue shift, was observed ( Figure 4B), thus confirming the previous findings by Quetglas et al (2000). In addition, no effect of Ca 2ϩ /calmodulin on SNARE complex formation was observed (Supplementary Figure S3).…”
Section: Binding Of Ca 2؉ /Calmodulin To Synaptobrevin Does Not Altersupporting
confidence: 79%
“…It has been shown previously that the C-terminal portion of the SNARE motif and the adjacent linker region, residues 77-90, constitutes a Ca 2ϩ -dependent binding site for calmodulin (Quetglas et al, 2000), raising the possibility that calmodulin controls the activity of synaptobrevin. To investigate this issue, we added Ca 2ϩ /calmodulin to a standard liposome fusion reaction, but no change of fusion rates was observed ( Figure 4A).…”
Section: Binding Of Ca 2؉ /Calmodulin To Synaptobrevin Does Not Altermentioning
confidence: 99%
“…Hence, the ability of syb2 mutants to support release in vivo reflects the contribution of each corresponding amino acid to the SNARE complex dimer interface. Previous studies have implicated W90 in calmodulin-dependent regulation of exocytosis (Quetglas et al, 2000(Quetglas et al, , 2002. However, because W90A would disrupt the calmodulin binding motif within syb2 (Rhoads and Friedberg, 1997;Chin and Means, 2000), the ability of this mutant to largely support secretion would suggest that such an interaction does not play a major role in vivo.…”
Section: Syb2 Dimerization Mutants Are Unable To Support Secretionmentioning
confidence: 89%
“…In either case, various structural and mutational data Rickman et al, 2006;Lynch et al, 2007) further indicate that residues distinct from those involved in dimerization seem to be responsible for complexin and synaptotagmin binding to SNARE complexes. W89 and W90 of syb2 have been implicated in binding to phospholipids (Quetglas et al, 2000(Quetglas et al, , 2002de Haro et al, 2004). In fact, it has been suggested that the reversible insertion of these residues of syb2 into the synaptic vesicle membrane may decrease the availability of syb2 and hence the probability of SNARE complex formation (Hu et al, 2002;Kweon et al, 2003).…”
Section: Dominant-negative Secretory Effects Of Syb2 Dimerization Mutmentioning
confidence: 99%
“…Ce même domaine de VAMP2 est connu pour son interaction avec la CaM. De plus, les mêmes déterminants moléculaires de la VAMP2 gouvernent son interaction avec la sous-unité c et la CaM [19]. Effectivement, nous avons aussi montré que l'interaction VAMP2/sousunité c est régulée par la Ca 2+ -CaM.…”
unclassified